Habitat Characteristics and Abundance of Mangrove Crabs in the Mangrove Forest of Concong Dalam Village in Concong District Indragiri Hilir Regency - David Aditya Simanjuntak; Syafruddin Nasution; Zulkifli Zulkifli (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2024)
This study was carried out in February 2024 in Concong Dalam Village, Concong District, Indragiri Hilir Regency, to know the habitat characteristics, types and distribution of abundance and size of mangrove crabs. This research uses a survey method by determining stations using purposive sampling consisting of 3 stations, where at each station, nine traps are installed with an area of around 628 m2/trap within 1 x 24 hours. Each trap is given chicken head bait in the morning at low tide, with two traps lifted at each high tide. A one-way ANOVA test was carried out to determine differences in abundance between stations. The results showed that the substrate was muddy with a moderate organic content of 12,82%. There were two species of mangrove crabs, including Scylla serrata and S.tranquebarica, where S. serrata dominated the population. The average abundance of mangrove crabs in the area was a value of 47,76 ind/ha, and there were no significant differences among stations. The size distribution of the species S. serrata (shell length 6-9,12 cm; shell width 9,08-13,31 cm; and weight 130-380 g), while in the species S. tranaubarica (shell length 6,52-6,98 cm; shell width 10,11-10,54 cm and weight 180 g). Small sizes dominated the population of mangrove crabs.